A New Regulatory Mechanism for Kv7.2 Protein During Neuropathy: Enhanced Transport from the Soma to Axonal Terminals of Injured Sensory Neurons - Cisneros, Elsa; Roza, Carolina; Jackson, Nieka; López-García, José Antonio (Frontiers in Cellular Neuroscience, 2015)
Kv7.2 channel expression has been reported to decrease in dorsal root ganglia (DRG) following the induction of a peripheral neuropathy while other experiments show that Kv7.2 accumulates in peripheral neuromas. The mechanisms underlying these novel expression patterns are poorly understood. Here we use immunofluorescence methods to analyze Kv7.2 protein expression in the sensory neurons following peripheral axotomy and the potential role of axonal transport. Results indicate that DRG neurons express Kv7.2 in ~ 16 % of neurons and that this number decreases by about 65 % after axotomy. Damaged neurons were identified in DRG by application of the tracer Fluoro-ruby at the site of injury during surgery. Reduction of Kv7.2 expression was particularly strong in damaged neurons although some loss was also found in putative uninjured neurons. In parallel to the decrease in the soma of axotomized sensory neurons, Kv7.2 accumulated at neuromatose fiber endings. Blockade of axonal transport with either vinblastine or colchicine abolished Kv7.2 redistribution in neuropathic animals. Channel distribution rearrangements did not occur following induction of inflammation in the hind paw. Behavioral tests indicate that protein rearrangements within sensory afferents are essential to the development of allodynia under neuropathic conditions. These results suggest that axotomy enhances axonal transport in injured sensory neurons, leading to a decrease of somatic expression of Kv7.2 protein and a concomitant accumulation in damaged fiber endings. Localized changes in channel expression patterns under pathological conditions may create novel opportunities for Kv7.2 channel openers to act as analgesics.